Convex combination framework for a priori SNR estimation in speech enhancement - Nahma, L.; Yong, P.; Dam, Hai Huyen Heidi; Nordholm, Sven (2017)
© 2017 IEEE. The paper proposes a convex combination fusion function based on a sigmoid function for the estimation of the a priori SNR in a speech enhancement framework with critical frequency band processing. The proposed method does not only eliminate the one frame delay generated by the well-known decision directed approach but also increases the adaptation speed during abrupt changes in the SNR estimation. As a result, the advantage of low musical noise has been maintained while more weak speech components have been preserved. Experimental results using instrumental and subjective measures also indicate improvement in speech quality compared to the reference methods.